2005
DOI: 10.1093/bja/aei059
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, phase III, controlled trial comparing levobupivacaine 0.25%, ropivacaine 0.25% and bupivacaine 0.25% by the caudal route in children †

Abstract: During sub-umbilical surgery, caudal levobupivacaine, ropivacaine and bupivacaine provided comparable analgesic efficacy. Bupivacaine produced a higher incidence of residual motor blockade and a longer analgesic block than ropivacaine and levobupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 20 publications
10
75
1
4
Order By: Relevance
“…For subumbilical surgery, Locatelli compared identical concentrations of caudally administered levobupivacaine, ropivacaine, and bupivacaine. Analgesic efficacy was similar among all three groups but bupivacaine resulted in a greater incidence of residual motor blockade and a longer analgesic block than the other two agents (18).…”
Section: Discussionmentioning
confidence: 79%
“…For subumbilical surgery, Locatelli compared identical concentrations of caudally administered levobupivacaine, ropivacaine, and bupivacaine. Analgesic efficacy was similar among all three groups but bupivacaine resulted in a greater incidence of residual motor blockade and a longer analgesic block than the other two agents (18).…”
Section: Discussionmentioning
confidence: 79%
“…Seventeen such RCTs were reviewed in detail using a structured methodology. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Two review articles were also identified. 18,19 The reference lists for all of these 19 publications were reviewed to identify any further RCTs that may have been missed with the initial search strategy; no such study was found.…”
Section: Methodsmentioning
confidence: 99%
“…Thirteen studies showed no difference in the duration; four studies showed a difference. Of these four, the first study 2 showed a longer duration of analgesia with bupivacaine compared with levobupivacaine or ropivacaine, as judged by Children's and Infant's Postoperative Pain Scale score and the need for analgesia. Somewhat predictably, the second study 5 showed a shorter duration of postoperative analgesia with 0.1% ropivacaine compared with 0.2% ropivacaine or bupivacaine.…”
Section: Relative Efficacymentioning
confidence: 99%
“…In the caudal block group, all children received a test dose of 0.2 ml.kg )1 bupivacaine 0.25% + epinephrine 1 : 200 000 followed by 0.8 ml.kg )1 bupivacaine 0.175%, whereas in the control group, no intervention took place. Finally, all children were turned back to the supine position and after 15 min the second set of measurements was performed; the effectiveness of the caudal block was assessed by pinching the skin at the level L1 and absence of movement was judged to be an effective block [7]. For the FRC measurements, an ultrasonic transit-time airflow meter (Exhalyzer D with ICU insert, Eco Medics, Duernten, Switzerland), which simultaneously measures flow and molar mass of the breathing gas, was placed between the fresh gas supply and the laryngeal mask airway.…”
Section: Methodsmentioning
confidence: 99%